2006
DOI: 10.1002/art.21654
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of murine collagen‐induced arthritis by the stress protein BiP via interleukin‐4–producing regulatory T cells: A novel function for an ancient protein

Abstract: Objective. Following the demonstration that the stress protein, BiP, prevented induction of collageninduced arthritis (CIA) in HLA-DRB*0101 ؉/؉ (HLA-DR1 ؉/؉ ) mice, we investigated the immunotherapeutic ability of BiP to suppress disease during the active phase of CIA in HLA-DR1 ؉/؉ and DBA/1 mice.Methods. BiP was administered either subcutaneously or intravenously to DBA/1, HLA-DR1 ؉/؉ , or interleukin-4 (IL-4)-knockout mice at the onset of arthritis. Immune cells were used in adoptive transfer studies or wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 29 publications
7
76
0
Order By: Relevance
“…Overproduction of IL-4 in NIT-GRP78-primed lymphocytes might then down-regulate the killing ability of Th1. Brownlie et al investigated the immunosuppressive function of GRP78 in arthritis, and found that GRP78 could suppress active collagen-induced arthritis by the induction of regulatory cells that act predominantly via IL-4 [28]. The results of the lowest necrosis in NIT-GRP78 cells cultured with NIT-GRP78-expanded lymphocytes, but a moderate necrosis cultured with NIT-EGFP-expanded lymphocytes, indicate that GRP78 might exert a protective and immunorepressive dual ability.…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of IL-4 in NIT-GRP78-primed lymphocytes might then down-regulate the killing ability of Th1. Brownlie et al investigated the immunosuppressive function of GRP78 in arthritis, and found that GRP78 could suppress active collagen-induced arthritis by the induction of regulatory cells that act predominantly via IL-4 [28]. The results of the lowest necrosis in NIT-GRP78 cells cultured with NIT-GRP78-expanded lymphocytes, but a moderate necrosis cultured with NIT-EGFP-expanded lymphocytes, indicate that GRP78 might exert a protective and immunorepressive dual ability.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of macrophages with SubAB inhibits LPS-induced MCP-1 and TNF-␣ expression and protects mice from LPS-induced sepsis and the development of experimental arthritis (28). Administration of BiP may also reduce collageninduced arthritis and is being considered a potential therapeutic agent in patients with rheumatoid arthritis (12). Reducing agents also protect cells from ER stress (32).…”
Section: Modulators Of Er Stressmentioning
confidence: 98%
“…However, it has recently become apparent that certain molecular chaperones such as HSP10 [17] and BiP [18] act to inhibit the pro-inflammatory actions of myeloid cells. Indeed, HSP10 has recently been shown to inhibit joint inflammation in patients with rheumatoid arthritis [19].…”
Section: Introductionmentioning
confidence: 99%